The orchid conservation challenge - Dixon, Kingsley (Universidad de Costa Rica, 2015)
In the six years since the first International Orchid Conservation Congress in 2001 has the conservation of orchids progressed? Certainly orchid science has grown from less than 100 published works in the 20 year period from 1900-1920 to over 3200 for 2000- 2005. With knowledge of orchids spanning an aston- ishing array of disciplines it is therefore surprising that there remains a significant gap between orchid science and orchid conservation practice.